ANALISIS ANGGARAN BIAYA TERHADAP EFISIENSI BIAYA PADA POKTAN SULTAN KUTO PADANG DI DESA BANDAR AGUNG KABUPATEN OKU - Andhika, Ryan; Anwar, Yuniarti; Wiralaga, Harby R (STIE DWI SAKTI BATURAJA, 2024)
The aim in this research is to find out whether the budget is efficient or not at the Sultan Kuto PadangPoktan in Bandar Agung Village, OKU Regency. The method used is the descriptive method usingobservation, documentation and interview data collection techniques. The data analysis technique used isQualitative analysis and Quantitative analysis, namely data obtained using quantitative descriptivetechniques which provide objective observation results on data obtained using a simple formula researchmodel for efficiency ratios and efficiency assessment criteria.After conducting research, it was found thatthe results of the 2019 Budget analysis of IDR 1,155,924,600.00 were realized at IDR 1,016,766,200.00, thisshows that there was a cost efficiency of IDR 139,158,400.00 or a percentage of 87%. Meanwhile, in the2020 budget, Rp. 881,375,180.00 was realized at Rp. 751,774,930.00 and showed an increase in efficiency ofRp. 129,600,250.00 or a percentage of 85%. The 2021 budget cost of IDR 1,023,429,440.00 was realized atIDR 819,976,296.00 and showed an increase in efficiency of IDR 203,453,144.00 or apercentage of 80%. Andthe 2022 budget of IDR 1,086,299,125.00 was realized at IDR 870,103,730.00 and showed an increase inefficiency of IDR 216,195,395.00 or a percentage of 80%.